The Society of Cancer Precision Medicine of Chinese Anti-Cancer Association - China Primary Health Care Foundation Tumor Precision Diagnosis and Treatment Committee; Chinese Anti-Cancer Association, Lung Cancer Study Group of Committee of Oncopathology (Chinese Journal of Lung Cancer, 2023)
RNA-based next-generation sequencing (NGS) has been recommended as a method for detecting fusion genes in non-small cell lung cancer (NSCLC) according to clinical practice guidelines and expert consensus. The primary targetable alterations in NSCLC consist of gene mutations and fusions, making the detection of gene mutations and fusions indispensable for assessing the feasibility of targeted therapies. Currently, the integration of DNA-based NGS and RNA-based NGS allows for simultaneous detection of gene mutations and fusions and has been partially implemented in clinical practice. However, standardized guidelines and criteria for the significance, application scenarios, and quality control of RNA-based NGS in fusion gene detection are still lacking in China. This consensus aims to provide further clarity on the practical significance, application scenarios, and quality control measures of RNA-based NGS in fusion gene detection. Additionally, it offers guiding recommendations to facilitate the clinical implementation of RNA-based NGS in the diagnosis and treatment of NSCLC, ultimately maximizing the benefits for patients from fusion gene detection.